Blow-up of Solutions to Porous Medium Equations with a Nonlocal Boundary Condition and a Moving Localized Source (Communications in Mathematical Research, 2021)
This paper is devoted to the blow-up properties of solutions to the porousmedium equations with a nonlocal boundary condition and a moving localized source.Conditions for the existence of global or blow-up solutions are obtained. Moreover,we prove that the unique solution has global blow-up property whenever blow-upoccurs.
Keywords: blow-up; moving localized source; nonlocal boundary condition; global blow-up.